The Influence of Motivation and Career Development on Employee Loyalty at PT Federal International Finance (FIFGROUP) Pematangsiantar Branch - Mhd. Ramadhan; Yudha Andika; Henny Gultom; Renni Sania; Amanda Aqilla (Journal of Management and Business Analytics, 2026)
This research aims to determine the level of motivation, career development, and employee loyalty at PT Federal International Finance (FIFGROUP) Pematang Siantar Branch, as well as to analyze the effect of motivation and career development on employee loyalty, both simultaneously and partially. The results of the study indicate that motivation and career development are in good condition, and employee loyalty is high. Furthermore, there is a positive influence, both simultaneously and partially, between motivation and career development on employee loyalty. The correlation between motivation, career development, and employee loyalty is moderately high, showing that the level of employee loyalty can be explained by these two factors. The results of hypothesis testing show that H₀ is rejected, meaning that motivation and career development have a positive and significant effect on employee loyalty at PT Federal International Finance (FIFGROUP) Pematang Siantar Branch.